2016
DOI: 10.1177/1053451216644823
|View full text |Cite
|
Sign up to set email alerts
|

Nine Tips for Creating an Effective Extended School Year Program for Students With Disabilities

Abstract: Extended school year (ESY) is a summer program available for students with disabilities who meet specific qualifying criteria. Teachers are often hesitant to accept the position of the ESY teacher due to the ambiguities and demands of the position. The purpose of this article is to briefly share the impetus and focus of ESY and give special education teachers nine tips to create and execute an effective ESY program. When implemented correctly, ESY programs have the potential to help students maintain learned s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In conclusion, school districts and cooperatives may be hesitant to provide ESY services due to cost (Osborne & Russo, 2009) and available qualified personnel (Sobeck, 2017) but Osborne and Russo (2009) have indicated that providing ESY services upfront is much more cost effective than reacting to litigation. Finally, other barriers may exist for schools in providing ESY services given the limited research in this area and that we limited our survey to the perceptions of special education directors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, school districts and cooperatives may be hesitant to provide ESY services due to cost (Osborne & Russo, 2009) and available qualified personnel (Sobeck, 2017) but Osborne and Russo (2009) have indicated that providing ESY services upfront is much more cost effective than reacting to litigation. Finally, other barriers may exist for schools in providing ESY services given the limited research in this area and that we limited our survey to the perceptions of special education directors.…”
Section: Resultsmentioning
confidence: 99%
“…The most often cited barrier reported by special education directors was difficulty in finding qualified personnel to work during the summer. With respect to qualified personnel, Sobeck (2017) noted that, “teachers are often hesitant to accept the position of the ESY teacher due to the ambiguities and demands of the position” (p. 170). This issue of determining eligibility for these services was the second most cited barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended school year (ESY) services refers to those special education supports and services provided beyond the typical 180-day school year (e.g., Burke & Decker, 2017; Queenan, 2015; Sobeck, 2017). The special education supports and services provided as part of ESY services are a continuation of the student’s Individualized Education Plan (IEP) over the summer break necessary to ensure that these students receive a free, appropriate public education (FAPE; Etscheidt, 2002).…”
mentioning
confidence: 99%
“…As a result, how LEAs determine eligibility for ESY services is quite varied. In determining eligibility for ESY services, the courts have suggested, but not required, a regression-recoupment standard for LEAs to apply (Burke & Decker, 2017; Sobeck, 2017). Under this standard, a student’s need for ESY services is a function of whether the student is deemed likely to “substantially regress” (Queenan, 2015, p. 168) over the summer break without being able to readily recoup those losses (i.e., typically within the first 6 weeks of school) (Queenan, 2012, 2015).…”
mentioning
confidence: 99%